When responsive and reactive meet organic? Treatment implications of language use in the era of #BanBPSD. (5th April 2021) - Macfarlane, Stephen; Atee, Mustafa; Morris, Thomas; Cunningham, Colm
Key points: The aetiopathogenesis of behaviours and psychological symptoms of dementia (BPSD) is often subjective, complex and multifaceted, produced by an array of contributing factors, including biomedical, psychological, environmental and/or social factors Alongside other contributing factors, organic aetiology of BPSD should be considered when devising therapeutic management plans Although considered last resort, time‐limited antipsychotic treatment (≤3 months) may have a vital adjunct role in managing intractable, refractory, distressing and/or life‐threatening BPSD, such as delusions and hallucinations; but only after person‐centred psychosocial interventions are exhausted and fail to deliver any therapeutic response If prescribed, careful monitoring of therapeutic responses and adverse effects of antipsychotics with de‐prescribing plans should be a top priority, as these agents have limited efficacies and serious adverse outcomes (e.g., mortality)